2004
DOI: 10.1080/08035250410025564
|View full text |Cite
|
Sign up to set email alerts
|

Reduced case fatality among hospitalized children during a war in Guinea-Bissau: a lesson in equity

Abstract: The decline in case fatality could be explained neither by a general decline in childhood mortality nor by changes in recruitment or discharge policy. The decline was therefore most likely due to improved treatment as a result of better availability of drugs funded by humanitarian aid and the presence of dedicated staff, which was offered relief food as compensation. Interventions improving case management may have a proportionately larger effect for poor families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…At the adjacent paediatric ward, the mere presence of dedicated staff has been associated with lower child mortality[ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the adjacent paediatric ward, the mere presence of dedicated staff has been associated with lower child mortality[ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four studies reported on urban, non-displaced populations living in armed conflict areas, of which one covered the acute emergency period (Bissau, Guinea Bissau, 1998-1999) [45] and three the post-emergency or early recovery period (Kabul [46] and Herat [47], Afghanistan, 2002-2003; Monrovia, Liberia, 2005 [48]).…”
Section: Resultsmentioning
confidence: 99%
“…The highest CFRs were noted among Sudanese refugees in Uganda (>30% in all but the youngest age group). In a paediatric ward in Guinea Bissau, pre-war CFR due to all diseases, and adjusted for various confounders, was higher than during the period of active fighting, possibly due to increased equity of care and availability of free drugs during the ensuing humanitarian response; the pneumonia CFR showed a similar trend (17.2% before the war, 13.1% during) [45]. This is unlikely to be due to self-selection of milder cases, as bed occupancy was actually higher during the war period.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it did not take the quality of the respective health care infrastructure or the health provision efforts of “exogenous” organizations such as the International Committee of the Red Cross (ICRC) or Médecins Sans Frontières (MSF) into consideration. In fact, the presence of organizations providing emergency relief can have major positive effects on human health in armed conflict settings [23].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that the complexity of all interactions may lead to counter-intuitive outcomes. For example, a marked decline in case fatality among hospitalized children was reported during a war in Guinea-Bissau, which was partly explained by improved treatment as a result of better access to drugs funded and distributed by humanitarian aid and non-governmental organizations [23].…”
Section: Methodsmentioning
confidence: 99%